Towards maturity a model of e-IIUM2WORLD scholarship for underprivileged students in Malaysia - Hakim, Lukmanul; Muhammad, Abdu; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2016)
Education is essential part for human being to advance new civilizations, while having better education definitely is aspiration of many students nowadays. Seeking knowledge in Islam is very important even mentioned in the holy Quran to “Iqra” which means read. Even though it is important, disadvantage students in Malaysia have some challenges to continue their studies into higher educations because of economic issues, and sometimes they struggle to make every endeavors in order to realize to study in the higher learning institution. To overcome students’ complaints on financial issues in their studies, the authors are collecting students’ feedback based on the e-IIUM2WORLD Business Model Canvas (BMC) and Value Proposition Design (VPD) of Islamic economic system from earlier work. A survey was conducted to understand students’ jobs, pains, and gains. This paper proposes a refined conceptual model of scholarship system that can be developed and implemented for underprivileged students, especially those who coming from rural areas that beyond from economic welfares.